Narrative Risk Premia: How Persistent Market Narratives Generate Volatility and Mispricing - Christodoulou-Volos, Christos (Journal of Cultural Analysis and Social Change, 2026)
This paper introduces the concept of narrative risk premia and presents empirical results indicating the presence of persistent narratives in financial markets, leading to excess volatility and mispricing. To further this concept, this research applies Robert J. Shiller’s narrative economics theory, advancing it from existing theories of market sentiment or information by creating a Market Narrative Intensity Index (MNII) based on the intensity of financial narratives within financial news, equity analyst reports, and financial communication within institutions. By integrating the index within theoretical structures of time series, asset pricing, and regime-switching, this research indicates narrative intensity shocks impacting volatility spikes, excessive returns, and narrative intensity-based risk premiums within the asset cross-section. The results indicate narrative effects exhibiting significant non-linear properties, regime dependency, narrative amplification in high narrative intensity states, and differences based on narratives centered on ‘fear’ or ‘hopefuls.’ These results provide alternative interpretations for volatility, market efficiency, and narratives as financial risk sources.